Chromatin organization drives the search mechanism of nuclear factors - Mazzocca, Matteo; Loffreda, Alessia; Colombo, Emanuele; Fillot, Tom; Gnani, Daniela; Falletta, Paola; Monteleone, Emanuele; Capozi, Serena; Bertrand, Edouard; Legube, Gaelle; Lavagnino, Zeno; Tacchetti, Carlo; et al. (Nature communications, 2023)
Nuclear factors rapidly scan the genome for their targets, but the role of nuclear organization in such search is uncharted. Here we analyzed how multiple factors explore chromatin, combining live-cell single-molecule tracking with multifocal structured illumination of DNA density. We find that factors displaying higher bound fractions sample DNA-dense regions more exhaustively. Focusing on the tumor-suppressor p53, we demonstrate that it searches for targets by alternating between rapid diffusion in the interchromatin compartment and compact sampling of chromatin dense regions. Efficient targeting requires balanced interactions with chromatin: fusing p53 with an exogenous intrinsically disordered region potentiates p53-mediated target gene activation at low concentrations, but leads to condensates at higher levels, derailing its search and downregulating transcription. Our findings highlight the role of disordered regions on factors search and showcase a powerful method to generate traffic maps of the eukaryotic nucleus to dissect how its organization guides nuclear factors action. Nuclear factors rapidly scan the genome for targets, but the role of nuclear organization in such search is uncharted. Here, by combining single molecule tracking of nuclear proteins with high resolution imaging of the nucleus, the authors investigate the search mechanism used by factors such as p53.